PENDIDIKAN KESEHATAN DETEKSI DINI KANKER PAYUDARA DENGAN MELAKUKAN ‘SADARI’ DI TP PKK DESA RAMBAH TENGAH HILIR KECAMATAN RAMBAH KABUPATEN ROKAN HULU - Nana Aldriana; Rahmi Fitria (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2022)
Breast cancer is a malignancy in breast tissue that can originate from the ductal epithelium or its lobules. Based on Pathological Based Registration in Indonesia, Breast cancer ranks first with a relative frequency of 18.6%. In Indonesia, more than 80% of cases are found to be in an advanced stage, where treatment is difficult. Therefore, it is necessary to understand the prevention efforts as the first step in preventing breast cancer before entering the final phase which is difficult to treat. Breast self-examination or SADARI until now is a way of early detection of breast cancer which is quite effective. SADARI is easy to do and can be applied to all ages, both teenagers and adult women. The purpose of this activity is to disseminate health education through BSE in TP PKK Desa Rambah Tengah Hilir Village, Rambah District for early detection of breast cancer in order to increase public knowledge in prevention and early treatment. The result of this service is the increasing knowledge of women of childbearing age in making efforts for breast cancer self-detection. In the end, it is hoped that activities like this can be carried out in other villages in Rambah District to further increase public knowledge in detecting breast cancer which is the most cancer in women.